Pengaruh Kepemilikan Institusional dan Komisaris Independen Terhadap Financial Distress Dengan Profitabilitas Sebagai Moderasi - Putri Maulidya; Endah Susilowati (Liquidity, 2025)
This study aims to examine the effect of institutional ownership and independent commissioners on financial distress, as well as the role of profitability in moderating this influence. The population used in this study were textile and garment sub-sector companies in 2019-2023 with a total sample of 16 companies. The analytical method used in this study is PLS-SEM using SmartPLS 3. The research findings show that institutional ownership has no effect on financial distress, independent commissioners have a positive effect on financial distress, profitability can moderate the effect of institutional ownership on financial distress, and profitability is unable to moderate the effect of independent commissioners on financial distress. The novelty of this research is to combine institutional ownership and independent commissioners on financial distress by adding profitability as moderating variable.